Players in the public policy process nonprofits as social capital and agents - Bryce, Herrington J. (Palgrave Macmillan, 2005)
"This book systematically develops the perspective of nonprofits or non-governmental organizations (NGOs) as social capital assets and agents of public policy within the principal-agent paradigm and across public purposes-foreign or domestic, religious or sectarian, in developed or developing countries. The perspective has universal applicability and allows us to go beyond assumptions of market or government failure. Morever, the perspective reflects the competitive situation in which nonprofits frequently find themselves when bidding against firms for government contracts." "The analysis identifies five factors that could offer nonprofits a clear, competitive advantage over firms and governments in certain contract bidding. The perspective yields a set of implications for the strategic positioning of nonprofits in the public policy arena, and yields a new functional classification that includes nonprofits (not merely as service providers), but as managers of significant social risks, as market and transaction regulators, and as centers of collective action along the full spectrum of public policy processes and issues."